Peningkatan Kesadaran Kesehatan Masyarakat melalui Penyuluhan dan Pemeriksaan Kesehatan di Pulau Pari, Kepulauan Seribu - Muhammad Maududi, Mukhlish; Said Romadlan; Dini Wahdiyati; Nu’aiman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This Community Service Program (PKM) aims to support the achievement of Sustainable Development Goal (SDG) No. 3 (Good Health and Well-Being) by raising public awareness of the importance of a healthy lifestyle. The program was conducted in Pari Island, Kepulauan Seribu, involving 30 participants from the local community. The activities included health screenings such as blood glucose measurement, blood pressure monitoring, and uric acid level testing, as well as health education on adopting a healthy lifestyle, including balanced nutrition and regular physical exercise. Through this initiative, participants gained a better understanding of how to maintain their health and prevent non-communicable diseases such as diabetes, hypertension, and uric acid disorders. The health screening results indicated that some participants had elevated blood glucose and blood pressure levels, highlighting the need for further intervention through education and lifestyle modifications. Increased awareness was evident from participants' enthusiasm during the health education sessions and interactive discussions with the facilitators. Overall, this program successfully enhanced community knowledge and awareness regarding the importance of a healthy lifestyle while also providing a concrete initial step through early health screenings. It is hoped that this program serves as a starting point for fostering a healthier and more prosperous community in Pari Island, supporting the achievement of SDG No. 3.